FRI0360 User's Experience of a Home- Based Fall-Detecting Device. (9th June 2015) - Nuñez, M.; Nuñez, E.; Lozano, L.; Sastre, S.; Garcia-Cardό, A.; Segur, J.M.; Salό, S.; Segura, V.; Sapena, N.; Alemany, X.; Montañana, J.; Cabestany, J.
Abstract : Background: Information and communications technologies (ICT) are being widely used in healthcare system. However, the real challenge is demonstrate their utility. Falls in the elderly and their consequences are increasing. We made an intervention to facilitate understanding of the user's experience in the context of a European research (The Fall Detector for the Elderly [FATE]) project to validate fall-detecting technology. FATE is a device that automatically detects falls in the elderly. Objectives: To extract information on patients' experience of the FATE system, a fall-detecting device that includes a mobile telephone and a fall-warning system, focusing on utility, and users' satisfaction. Methods: Type of intervention: Guided group dynamics. Theoretical framework: systematic use of active learning, design thinking, role-playing and thematic analysis. Scenarios: The experience was developed using 3 simulated scenarios that included patients, relatives and investigators. Sample: Twenty-five patients currently using the device were included. Mean age 76 (SD 7) years, BMI 30 (DE 6). All patients had ≥3 chronic condition of which the most frequent were osteoarthritis (100%) hypertension (55%), osteoporosis (46%), depression (45.5%), urinary incontinency (36%), high cholesterol (32%), medications mean 6 (DE 2.3). Timed Up and Go (TUG) test 20.4 (DE 5) seconds (80% ≥13.5 seconds). Group dynamics: Five participants were selected from the 25 patients. Five unrelated relatives were chosen. Three investigators actively participated only in the third and final stage of the dynamics 1, 2 . Results: Areas for improvement . These included reducing the distance between the mobile phone and the warning-alarm device, improving the device's sensitivity, improving teaching of handling of the mobile and 17 other recommendations which can be summed up as: Coverage: Faster, easier access to device functions; measurement of other health-related data; concentration/expansion of access points. Sensitivity: Adjustments in sensitivity of the response; increased autonomy and energy balance; adaptation of the alarm system (sound + lighting + message). Safety: Incorporation of customer service; dynamic customization; more-precise attachment and antitheft system. Control: Reinforcing training and tutorials; increased social transparency and dissemination of knowledge; implementation of study on the psycho-sociological impact. Integration: unification of the device in a single appliance; application of trust-building systems; involvement of all stakeholders in research. Conclusions: Users and relatives, in a proactive process using simulated scenarios, identified problems, solutions and areas for improvement. This collaborative work produced valuable solutions better adapted to the real needs of users. References: http://pracmatic.net/patient-empowerment/ http://youtu.be/dLYw984FiYQ Acknowledgements: The FATE project has been funded by CIPICT-PSP-2011-5 297178 Disclosure of Interest: None declared